2021
DOI: 10.1016/j.ypmed.2021.106564
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted strategies for the control of COVID-19 outbreaks in long-term care facilities in Ontario, Canada

Abstract: The novel coronavirus disease 2019 (COVID-19) has caused severe outbreaks in Canadian long-term care facilities (LTCFs). In Canada, over 80% of COVID-19 deaths during the first pandemic wave occurred in LTCFs. We sought to evaluate the effect of mitigation measures in LTCFs including frequent testing of staff, and vaccination of staff and residents. We developed an agent-based transmission model and parameterized it with disease-specific estimates, temporal sensitivity of nasopharyngeal and saliva testing, res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 46 publications
0
36
0
Order By: Relevance
“…Fatehi et al ( 2021 ) evaluated the effectiveness of two forms of therapies, that is, remdesivir and convalescent plasma (CP) therapy. Forty‐five papers evaluated the impacts of different NPIs on COVID‐19 containment in specific organizations, including elementary or secondary schools (Asgary et al, 2021 ; Morrison et al, 2021 ; Zafarnejad & Griffin, 2021 ), colleges and universities (Bahl et al, 2021 ; Brennan et al, 2021 ; Goyal et al, 2021 ; Kharkwal et al, 2021 ; Lv et al, 2021 ), hospital (Campos et al, 2022 ; Huang et al, 2021 ; Mukherjee et al, 2021 ), army training post (Espana et al, 2021 ), refugee camp (Gilman et al, 2020 ), nursing and care home (Holmdahl et al, 2021 , 2022 ; Kahn et al, 2022 ; Lasser et al, 2021 ; Nguyen et al, 2021 ; Stevenson et al, 2021 ), long‐term care facility (Vilches et al, 2021 ), church (Rothrock et al, 2021 ), supermarket (Tong et al, 2021 ) and construction site (Alzu’bi et al, 2021 ). Three of them explored the effects of NPIs on special events, including two rituals of the Hajj (Al‐Shaery et al, 2021 ), wedding ceremony (Alzu’bi et al, 2021 ) and indoor gathering (Farthing & Lanzas, 2021b ).…”
Section: Resultsmentioning
confidence: 99%
“…Fatehi et al ( 2021 ) evaluated the effectiveness of two forms of therapies, that is, remdesivir and convalescent plasma (CP) therapy. Forty‐five papers evaluated the impacts of different NPIs on COVID‐19 containment in specific organizations, including elementary or secondary schools (Asgary et al, 2021 ; Morrison et al, 2021 ; Zafarnejad & Griffin, 2021 ), colleges and universities (Bahl et al, 2021 ; Brennan et al, 2021 ; Goyal et al, 2021 ; Kharkwal et al, 2021 ; Lv et al, 2021 ), hospital (Campos et al, 2022 ; Huang et al, 2021 ; Mukherjee et al, 2021 ), army training post (Espana et al, 2021 ), refugee camp (Gilman et al, 2020 ), nursing and care home (Holmdahl et al, 2021 , 2022 ; Kahn et al, 2022 ; Lasser et al, 2021 ; Nguyen et al, 2021 ; Stevenson et al, 2021 ), long‐term care facility (Vilches et al, 2021 ), church (Rothrock et al, 2021 ), supermarket (Tong et al, 2021 ) and construction site (Alzu’bi et al, 2021 ). Three of them explored the effects of NPIs on special events, including two rituals of the Hajj (Al‐Shaery et al, 2021 ), wedding ceremony (Alzu’bi et al, 2021 ) and indoor gathering (Farthing & Lanzas, 2021b ).…”
Section: Resultsmentioning
confidence: 99%
“…10 11 Yet, Canada's testing capacity has been limited to symptom-based screening. 12 This situation may have serious repercussion on the country's capacity to effectively control the disease in the wake of yet another wave of COVID-19, hence, warranting the need for a study that examines the association between self-reported symptoms and testing for COVID-19 in Canada. Despite Canada's relative success in containing the spread of COVID-19, little attention has been paid to assess its COVID-19 testing strategy.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…There has been extensive analysis and evaluation of the optimal strategies for both RT-PCR and RA testing to mitigate SARS CoV-2 transmission 4 6 , 8 – 18 , 36 , 37 . However, most of these analyses do not quantify the degree to which their use suppresses individual-level transmission in applications of quarantine 36 or serial surveillance testing with isolation of positives 10 , 11 , 13 , 15 , 16 , and most address a generalized or single RA test 5 , 6 , 9 , 11 , 12 , 16 , 18 , 36 , 37 , or focus only on RT-PCR 4 , 8 , 10 , 13 , 15 , 17 . In contrast, multiple RA tests have received regulatory Emergency Use Authorization (EUA) 38 , each with distinct temporal diagnostic sensitivity.…”
Section: Introductionmentioning
confidence: 99%